Langur monkey's day - Hammerslough, Jane; Buelt, Laura; Galvin, Laura Gates; Kinon, Jennifer; Pilchowski, Marcin D; Shriver, Chelsea (London Sound Prints, 2003)
A young Hanuman langur spends her day in a national park in India by eating, drinking, holding the monkey troop's new baby, and observing various other animals
Science (Animals)
Keywords: Animals